Competition and investment in the Danish broadband market - Ilsa Godlovich; Sonia Strube Martins; Christian Wernick (WIK-Consult GmbH, 2019)
New legislative provisions on "symmetric" access regulation are due to be introduced in Denmark, in the context of the transposition of the 2018 EU Electronic Communications Code. Symmetric access obligations under the Code are obligations that apply to all operators, and not only to operators found to have "Significant Market Power". In this report, the state of competition on the Danish broadband market is analyzed. we assess the impact that different forms of "symmetric" wholesale access regulation may have on the investment incentives of broadband operators in Denmark, as well as the potential effects on competition and consumer outcomes. – – Neue gesetzliche Bestimmungen zur "symmetrischen" Zugangsregelung sollen in Dänemark im Rahmen der Umsetzung des europäischen Kodex für die elektronische Kommunikation (EKEK) von 2018 eingeführt werden. Dabei handelt es sich um Zugangsverpflichtungen, die für alle Betreiber gelten, und nicht nur für Betreiber, die als SMP-Betreiber eingestuft wurden. In der Studie untersuchen wir die Wettbewerbssituation auf dem dänischen Breitbandmarkt und bewerten die Auswirkungen, die verschiedene Formen der "symmetrischen" Regulierung des Zugangs auf der Vorleistungsebene auf die Investitionsanreize von Breitbandnetzbetreibern in Dänemark haben können. Darüber hinaus untersuchen wir die potenziellen Auswirkungen auf den Wettbewerb und die Ergebnisse für die Verbraucher.
Additional information: Study for Energistyrelsen
Keywords: 330; Breitbandkommunikation; Wettbewerbsanalyse; Investitionsentscheidung; Branchenentwicklung; Dänemark